AN INVESTIGATION OF MARINE TOURISM AT TUREDAWOLA BEACH - Harefa , Afore Tahir; Harefa , Sevtryani; Gulo, Jernita; Zalukhu, Jepriaman (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Marine tourism is a strategic sector in coastal development, yet its management is often not optimal. This study aims to analyze the development and promotion of marine tourism at Turedawola Beach, North Nias Regency, and to identify the gap between sustainable marine tourism theory and actual field conditions. This research employed a qualitative descriptive approach, with data collected through interviews, observations, and documentation. The findings indicate that marine tourism activities at Turedawola Beach remain limited to surfing and basic beach recreation, despite the area’s strong natural potential, particularly its internationally recognized surfing waves. The main challenges identified include limited tourism facilities, low human resource capacity, minimal structured community involvement, and tourism promotion that has not been effectively managed through digital platforms. These findings reveal a clear gap between the concept of sustainable marine tourism and existing management practices. Therefore, collaboration among the government, local communities, and the private sector is essential to improve management, promotion, and the sustainability of marine tourism at Turedawola Beach.